Advanced printable hydrogels from pre-crosslinked alginate as a new tool in semi solid extrusion 3D printing process. (15th January 2022) - Falcone, Giovanni; Mazzei, Pierluigi; Piccolo, Alessandro; Esposito, Tiziana; Mencherini, Teresa; Aquino, Rita P.; Del Gaudio, Pasquale; Russo, Paola
Abstract: With the aim to overcome alginate shape fidelity issue during the semisolid extrusion 3D printing and matrix collapsing after drying, we speculated that a pre-crosslinking step of the alginate ink-gel with low amount of Ca +2 could improve the hydrogel performance. To verify this, the influence of pre-crosslinker concentration (10–25 mM) on the ink gel rheological properties were studied and flow behaviour and viscoelastic properties were determined. The developed ink gels were fully characterised by DSC and Magnetic Resonance Imaging (MRI). Moreover, extrudability and the shape retention of extruded forms after printing and after drying were studied. The rheological and MRI data, combined with the morphological analysis of printed forms allowed us to identify the relationship between printability, shape retention and shear thinning behaviour of gels, showing good extrudability for all the pre-crosslinked gels with a calcium concentration between 0.15 and 0.25, corresponding to both egg-box dimers and multimers interactions. Graphical abstract: Unlabelled Image